(untitled) (Ciencias de la Ingeniería y Aplicadas, 2018)
Rational thermal insulation thickness parameters for heavy crude oil conductive pipes are established, taking into account economic and technical criteria; For this, the influence of the insulation thickness on the energy losses for different pipe diameters is taken into consideration. The results showed that for oil transportation systems, the rational insulation thickness is 0.08 m for all pipe diameters that are in the range between 0.08 and 0.3 m, based on energy costs, the thermophysical properties of the fluid and the components of the conductor.